THE IMPLEMENTATION OF INVENTORY CONTROL USING ECONOMIC ORDER QUANTITY METHOD IN IMPROVING THE COST EFFICIENCY OF RAW MATERIALS AND INVENTORY TURNOVER OF THE COMPANY (CASE STUDY IN PT HERLINAH CIPTA PRATAMA) - Dina Aprilianti; Jouzar Farouq Ishak (KRISNA: Kumpulan Riset Akuntansi, 2023)
Inventory has an important role in the smooth production process of the company. Inventory control becomes necessary to do so that the company's operations run according to plan and operational costs can be minimized. This study focuses on knowing the cost efficiency of raw material inventory and inventory turnover at PT HerlinahCiptaPratama by using the Economic Order Quantity (EOQ) method so that the optimal order quantity and the right time in the procurement of raw material inventory can be known. The type of research used is descriptive quantitative with case study method. Sources of data used are primary data obtained through interviews and observations, and secondary data obtained through documentation from archives, records, and company reports. The results of this study indicate that the application of the Economic Order Quantity method in inventory control can increase the cost efficiency of the company's raw material inventory in 2018-2020. This cost efficiency is reflected in the total cost of inventory using the Economic Order Quantity method, which is lower than the total cost of the conventional method of inventory, thus indicating a savings in inventory costs. However, the application of the Economic Order Quantity method does not fully increase the inventory turnover value of all PT HerlinahCiptaPratama raw materials in 2018-2020 because the accumulation of purchases according to the EOQ method in a certain period is greater than the conventional method so that the ending inventory is higher.